Effect of barium substitution on phase transitions of lead barium zirconate ceramics prepared by solid state reaction method - Gobwute Rujijanagul (2018)
The effect of Ba2+substitution on the phase transitions of (Pb1-xBax)ZrO3(PBZ) ceramics (0.0≤x≤0.30) has been investigated as a function of x. Phase formation and phase transition of PBZ were investigated by x-ray diffraction (XRD) and thermal analysis, respectively. It was found that the structure of sintered pellets is orthorhombic for 0.0≤x≤0.10 and rhombohedral for 0.20≤x≤0.30, whereas orthorhombic and rhombohedral phases coexist at x = 0.15. The proportion of ferroelectric and paraelectric phase in the samples gradually decreased with increasing Ba2+content.